Career expectations and influences among dental students in Malaysia - Che Musa, Muhd Firdaus; Bernabe, Eduardo; Gallagher, Jennifer E. (John Wiley & Sons, Inc, 2016)
Introduction: It is important to understand career expectations of emerging dental graduates if human resources are to be harnessed in support of oral health. The aims of this study were to explore students' career expectations and their perceived influences, and to examine variation according to student and school characteristics. Methods: All final-year students registered for 2013/2014 across 11 dental schools in Malaysia were invited to participate in a self-administered questionnaire (n = 530). The instrument explored short- and long-term career expectations, influences and students' background using a mix of open- and closed-ended questions. The chi-square test was used for comparison according to student and school characteristics. Results: Three-hundred and fifty-six (83%) students, across eight schools, completed the questionnaire. In the short term, undertaking specialist training (46%) was the most commonly cited career goal, and achieving financial stability (79%) was the greatest influence. In the long term, 59% planned to specialise (with a significant difference found according to ethnic group), and 67% considered working full-time, with men significantly more likely to do so than women (P = 0.036). More Malay students (90%) ranked childcare commitments as an important influence on the number of sessions they planned to work per week compared with Chinese students (75%) and Others (74%; P = 0.001). Work–life balance (95%) and high income/financial security (95%) were the main influences on respondents' long-term goals. Conclusion: There was a high level of interest in specialisation and a desire to achieve financial stability and work–life balance in the group of dental students who responded to the survey. Long-term career expectations varied according to student but not according to school characteristics.